Understood or Forced: Reviewing Lecturers' Interest in Saving in Islamic Banks - Kurniasih Setyagustina; Nur Khasanah; Ahmadi Ahmadi; Winahyu Dwi Suhitasari; Rina Nurarifah (Journal Of Sharia Banking, 2023)
Understanding Islamic banking can be applied properly but has not fully positively influenced the intention to save in Islamic banking. Lack of interest and customer trust in Islamic banking to save in Islamic banking so there is a need for socialization of Islamic banking knowledge itself, both regarding understanding, of products, principles, and contracts used by parties from Islamic banks. In addition, some opinions also state that it is normal for lecturers at Islamic religious colleges to save in Islamic banks because they are required to open savings accounts to receive their salary through Islamic banks. Based on the description of the problem, the researcher is interested in conducting further research to prove whether the understanding of Islamic banking on lecturers' interest in saving in Islamic banking can maximize or have a positive effect on saving or not saving in Islamic banks. The discussion of this research relates to the field of science in connection with that the approach taken in theories related to understanding and interest. This research is quantitative. The samples used in this study were 34 lecturers. Data collection techniques used are interview techniques, distributing questionnaires, and documentation. The analysis technique of this research uses a validity test, reliability test, normality test, linearity test, classical assumption test, simple linear regression test, and hypothesis test with the help of SPSS version 26 software. The results of the study show that lecturer knowledge influences people's interest in saving at Islamic banks. This of course can prove that Indonesian Islamic banks have a place in the hearts of lecturers, not only because of the obligation to open an account at an Islamic bank to get a salary as a lecturer.